Mono and dual agonists of the amylin, calcitonin, and CGRP receptors and their potential in metabolic diseases - Nina Sonne; Morten A. Karsdal; Kim Henriksen (Molecular Metabolism, 2021)
Background: Therapies for metabolic diseases are numerous, yet improving insulin sensitivity beyond that induced by weight loss remains challenging. Therefore, search continues for novel treatment candidates that can stimulate insulin sensitivity and increase weight loss efficacy in combination with current treatment options. Calcitonin gene-related peptide (CGRP) and amylin belong to the same peptide family and have been explored as treatments for metabolic diseases. However, their full potential remains controversial. Scope of review: In this article, we introduce this rather complex peptide family and its corresponding receptors. We discuss the physiology of the peptides with a focus on metabolism and insulin sensitivity. We also thoroughly review the pharmacological potential of amylin, calcitonin, CGRP, and peptide derivatives as treatments for metabolic diseases, emphasizing their ability to increase insulin sensitivity based on preclinical and clinical studies. Major conclusions: Amylin receptor agonists and dual amylin and calcitonin receptor agonists are relevant treatment candidates, especially because they increase insulin sensitivity while also assisting weight loss, and their unique mode of action complements incretin-based therapies. However, CGRP and its derivatives seem to have only modest if any metabolic effects and are no longer of interest as therapies for metabolic diseases.